The crucible of COVID-19: what the pandemic is teaching us about health research systems - Tari Turner; Fadi El-Jardali (BMC, 2020)
Abstract The global health crisis created by COVID-19 is providing valuable insights into the strengths of our health research system and, perhaps even more clearly, displaying its weaknesses. Much of what is being shown so plainly in the current context is not truly new. We are being reminded that health research systems are slow and noisy as well as that there is a desire for research to inform decision-making, that researchers are great collaborators, and that the walls we are so quick to erect between health research and health practice are unhelpful facades. It is our hope that the clarity with which these issues are being demonstrated by COVID-19 might provide the impetus to address these challenges and seize these opportunities to improve our health research system, for the benefit for communities facing COVID-19 now, and for the benefit of us all in facing the further health challenges that are sure to come.